A Retrospective Study of Clinical Spectrum and Treatment Outcomes of Hiv Associated Cancers In A Tertiary Care Centre - Dr. T. Rethinesh Kumar; Dr. B. Jabapriya; Dr. A. Kodies, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction: With the introduction and widespread availability of highly active anti-retroviral therapy (HAART), the landscape of HIV/AIDS has changed considerably. This is true for HIV-associated malignancies as well. Post-HAART, the incidence of Kaposi's sarcoma and central nervous system (CNS) lymphoma (among AIDS-defining cancers) decreased in parallel with AIDS-defining infections. On the other hand, the incidence of systemic non-Hodgkin's lymphoma (NHL) and cervical cancer decreased less than others and remains higher in HIV-infected patients than in the general population. Materials and methods: The study was a retrospective observational study which included all the patients with HIV and cancer attending the Oncology Department OPD Department of Radiation Oncology, Government Madurai Medical College, Madurai between January 2024 and December 2024. Data obtained from the case records was used to fill up the proforma which included the patient factors (Age, sex, performance status, BMI, substance abuse), HIV related parameters (Time since diagnosis of HIV, baseline CD4 counts, comorbid conditions, treatment with HAART), tumour related factors (Site, type of cancer, subtype, stage, prognostic factors depending on the histology) and treatment aspects (Type of treatment, any requirement of dose modifications, toxicity, response, compliance). Results: The study included 200 patients with HIV and cancer (86 female patients and 114 male patients) with an average age of 42 years. A majority of the patients (39%) were in the 31-40 years age group. The mean BMI of the study group was 19.45 (Range: 10 -26.5). 59 of the 200 patients (29.5 %) had poor general condition with a performance status of 3 or 4 by the ECOG (Eastern Cooperative Oncology Group) scale. All patients were already enrolled for anti-retroviral therapy. The mean time to presentation of cancer after the diagnosis of HIV infection was 5.4 years (Range: 2 months to 15 years). 122 patients had Non-AIDS Defining Cancers (NADC) and 78 had AIDS defining cancers (ADC). Conclusion: In the HAART era, NADCs are more common than ADCs. The most common malignancy in HIV patients is NHL, with DLBCL (Diffuse Large B-Cell Lymphoma) subtype being the commonest in this study. Extranodal presentations are more common than nodal presentation. Standard chemotherapyachieves a response rate of 50% in HIV-NHL cases and 46% in HIV patients with solid cancers. The study illustrates the need for prolonged surveillance for the development of cancer in HIV patients. Early initiation of HAART, optimal chemotherapeutic regimens, radiotherapy protocols, appropriate palliative care and nutritional support should form an integral part of the care of HIV patients with cancer.